2011
DOI: 10.5007/1980-0037.2010v12n2p90
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de obesidade em escolares de 7 a 12 anos de uma cidade Serrana do RS, Brasil DOI:10.5007/1980-0037.2010v12n2p90

Abstract: Rev Bras Cineantropom Desempenho Hum 2010, 12(2):90-97Resumo -A obesidade e o sobrepeso vêm aumentando suas prevalências em todo o mundo nos últimos anos. O objetivo do presente estudo foi estimar a prevalência de obesidade e sobrepeso em escolares de 7 a 12 anos (meninos e meninas), de uma cidade serrana do RS e verificar as possíveis associações com as seguintes variáveis: classe socioeconômica, aptidão aeróbica, hábitos alimentares e hábitos de lazer (sedentários e atividade física). Foram avaliados 1.442 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
30

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 13 publications
1
9
0
30
Order By: Relevance
“…The main risks to the health of obese children are hyperlipidaemia, systemic hypertension, and psychological source of damage because obese children are discriminated against 21. A prevalence of 5.08% of obesity in children from AC and 9.36% in children from RS was found. These findings are similar to the results of Rech et al 22 , who researched schoolchildren aged 7 to 12 years on a mountain city of RS and found obesity rates of 7.4%, 8.4%, 7.2% and 9.8% for children 7, 8, 9 and 10 years, respectively. Oliveira et al 23 found that there was a positive association between high levels of parental education, high family income, and presence of home appliances such as TV, computer and video game with obesity.…”
Section: Discussionsupporting
confidence: 81%
“…The main risks to the health of obese children are hyperlipidaemia, systemic hypertension, and psychological source of damage because obese children are discriminated against 21. A prevalence of 5.08% of obesity in children from AC and 9.36% in children from RS was found. These findings are similar to the results of Rech et al 22 , who researched schoolchildren aged 7 to 12 years on a mountain city of RS and found obesity rates of 7.4%, 8.4%, 7.2% and 9.8% for children 7, 8, 9 and 10 years, respectively. Oliveira et al 23 found that there was a positive association between high levels of parental education, high family income, and presence of home appliances such as TV, computer and video game with obesity.…”
Section: Discussionsupporting
confidence: 81%
“…De acordo com Guimarães et al 32 , crianças e adolescentes residentes em domicílios com nove ou mais equipamentos domésticos apresentam 3,2 vezes mais risco para o sobrepeso. Rech et al 33 e Suñé et al 18 relatam que possuir televisão, vídeo game e computador implica hábitos sedentários e, mesmo após controle na análise de regressão múltipla, relaciona-se a elevadas prevalências do excesso de peso.…”
Section: Discussionunclassified
“…Estudo feito em SC, na cidade de Indaial, com 259 escolares com idade entre 8 e 10 anos, também obteve resultados semelhantes aos do presente estudo, em relação ao sobrepeso, identificando 24,4% no sexo feminino e 17,7% no sexo masculino 15 . Outro estudo semelhante, de Rech et al 16 , mostrou que 27,9% dos escolares de ambos os sexos estavam acima do peso.…”
Section: Discussionunclassified